Hepatic Abscess After Pancreatic Extracorporeal Shock Wave Lithotripsy. Issue 10 (18th October 2022) - Ramsey, Mitchell L.; Bender, Matthew; Lara, Luis F.; Han, Samuel
ABSTRACT: We report the case of a 61-year-old woman with painful chronic pancreatitis related to proximal pancreatic duct pancreatolithiasis who underwent successful fragmentation with pancreatic extracorporeal shock wave lithotripsy (ESWL). Two weeks later, she developed abdominal pain, nausea, and vomiting and was found to have a new 4.6 × 2.3 cm hepatic abscess. She was treated with antibiotics but did not require additional intervention. Reported etiologies of post-ESWL abdominal pain include local irritation and bruising at the interface and pancreatitis, which has been reported in 4.2% of cases. We suggest that hepatic abscess ought to be considered in the differential diagnosis of post-ESWL abdominal pain.